(untitled) (Journal of Educational Sciences, 2022)
The article will focus on the transformation to our country of the positive experience of the system of certification of teaching staff in Singapore and Finland. The current state of pedagogical certification of pedagogical personnel in Kazakhstan was also considered. Thanks to the certification of teachers, along with the training of general practice teachers and persons equated to teachers, this contributes to improving the level of education taking into account national literacy. The rules approved by the order of the Ministry of Education and Science of the Republic of Kazakhstan set the terms of certification of teachers in accordance with the legislation. According to the results of the certification in accordance with these times and rules, teachers are divided into different categories and degrees. The article discusses the features of the teacher certification procedure, its perception by teachers, the impact on the status of teachers in the teaching staff. The difficulties that certification causes in the professional activity of a teacher, the ways in which these problems can be solved are also indicated. And in such an important activity, we use the best world experience. We present the results of a survey in which 68 teachers took part. The purpose of the survey is to determine what difficulties exist in the certification process at the present time. The survey was conducted online on the Google Workspace platform. Based on the results, we drew conclusions and showed what experience can be gained in our country from such highly educated countries as Singapore and Finland. Key words: Singapore, Finland, teaching staff, certification, transformation, questionnaire.